3D printed scaffold for repairing bone defects in apical periodontitis - Cong Li; Xiaoyin Xu; Jing Gao; Xiaoyan Zhang; Yao Chen; Ruixin Li; Jing Shen (BMC, 2022)
Abstract Objectives To investigate the feasibility of the 3D printed scaffold for periapical bone defects. Methods In this study, antimicrobial peptide KSL-W-loaded PLGA sustainable-release microspheres (KSL-W@PLGA) were firstly prepared followed by assessing the drug release behavior and bacteriostatic ability against Enterococcus faecalis and Porphyromonas gingivalis. After that, we demonstrated that KSL-W@PLGA/collagen (COL)/silk fibroin (SF)/nano-hydroxyapatite (nHA) (COL/SF/nHA) scaffold via 3D-printing technique exhibited significantly good biocompatibility and osteoconductive property. The scaffold was characterized as to pore size, porosity, water absorption expansion rate and mechanical properties. Moreover, MC3T3-E1 cells were seeded into sterile scaffold materials and investigated by CCK-8, SEM and HE staining. In the animal experiment section, we constructed bone defect models of the mandible and evaluated its effect on bone formation. The Japanese white rabbits were killed at 1 and 2 months after surgery, the cone beam computerized tomography (CBCT) and micro-CT scanning, as well as HE and Masson staining analysis were performed on the samples of the operation area, respectively. Data analysis was done using ANOVA and LSD tests. (α = 0.05). Results We observed that the KSL-W@PLGA sustainable-release microspheres prepared in the experiment were uniform in morphology and could gradually release the antimicrobial peptide (KSL-W), which had a long-term antibacterial effect for at least up to 10 days. HE staining and SEM showed that the scaffold had good biocompatibility, which was conducive to the adhesion and proliferation of MC3T3-E1 cells. The porosity and water absorption of the scaffold were (81.96 ± 1.83)% and (458.29 ± 29.79)%, respectively. Histological and radiographic studies showed that the bone healing efficacy of the scaffold was satisfactory. Conclusions The KSL-W@PLGA/COL/SF/nHA scaffold possessed good biocompatibility and bone repairing ability, and had potential applications in repairing infected bone defects. Clinical significance The 3D printed scaffold not only has an antibacterial effect, but can also promote bone tissue formation, which provides an alternative therapy option in apical periodontitis.